Association of health promotion behaviors with frailty in Chinese middle-aged and older adults: a cross-sectional study - Yifei Chen; Xi Chen; Yinan Zhao; Lina Wu; Dian Jiang; Fenghui Chen; Hui Feng (BMC Geriatrics)
Abstract Background Frailty as an age-related health state poses a challenge to healthy aging, but as a reversible state has the opportunity to be modified. However, the effectiveness of health promotion interventions currently implemented for frailty remains unclear. Therefore, we aimed to explore the association between multidimensional health promotion behaviors and frailty in Chinese middle-aged and older adults, as well as gender and age differences in this association to provide key entry points to address frailty. Methods We conducted a cross-sectional study using survey data from the Chinese Longitudinal Healthy Longevity Survey in 2018. We included participants aged 60 years or older who had complete frailty index and health promotion behavior items. Based on the definition proposed by Pender, we constructed six dimensions of health promotion behaviors and standardized the data using the Z-Score. Multinomial logistic regression models were used to assess the association between health promotion behaviors and frailty states, and we employed multiple linear regression analysis to investigate the correlation between health promotion behaviors and age among middle-aged and older adults of different genders. Results Among the 10,388 participants, 4,447 (42.8%) were categorized as robust, 3,623 (34.9%) were categorized as pre-frail, and 2,318 (22.3%) were categorized as frail. Frail individuals were older, predominantly female, had more comorbidities, had poorer self-reported health and quality of life, experienced more socioeconomic disadvantages, and exhibited lower levels of health promotion behaviors compared to the robust and the pre-frail. In the full-adjusted model, nutritional behaviors and physical activities lower frailty and pre-frailty risk, while stress management and interpersonal support were significantly associated with higher frailty and pre-frailty odds. No significant associations were observed between total health promotion behavior scores with frailty states. Conclusion Multidimensional health promotion behaviors are critical factors in the frailty status of Chinese middle-aged and older adults, and there are gender differences in the age-dependent trends in the levels of health promotion behaviors among them with different frailty states. This informs the provision of targeted prevention and intervention services for middle-aged and older adults.